International financial governance under stress : global structures versus national imperatives - Underhill, Geoffrey R. D.; Zhang, Xiaoke (Cambridge University Press, 2003)
The Asian and Argentinian financial crises have focused attention on the most appropriate shape and role for international and national financial institutions. This volume offers a wide-ranging overview of the problems and possible policy responses. Although the approach is multi-disciplinary, most of the contributors write from a political economy perspective.
Based on an international conference held Feb. 3-5, 2000 in Amsterdam.
Keywords: International finance -- Congresses.; Financial crises -- Congresses.; Monetary policy -- Congresses.; Financial crises -- Asia -- Congresses.; Monetary policy -- Asia -- Congresses.; Politique monétaire -- Congrès.; Politique monétaire -- Asie -- Congrès.; BUSINESS & ECONOMICS -- Finance.; International finance.; Financial crises.; Monetary policy.; International finance -- Asia.; Financial crises -- Asia.; Monetary policy -- Asia.; Financial crises; International finance; Monetary policy; Asia; Financieel beleid.; Financiële crises.; Electronic books.; Conference papers and proceedings